Comparative Study on Jejunal Immunity and Microbial Composition of Growing-Period Tibetan Pigs and Duroc × (Landrace × Yorkshire) Pigs - Yang, Yuting; Li, Yongxiang; Xie, Yanggang; Qiao, Shiyan; Yang, Lijie; Pan, Hongbin (Frontiers in Veterinary Science, 2022)
The gut microbiota plays vital roles in metabolizing nutrient, maintaining the intestinal epithelial barrier but also in modulating immunity. Host genetics and the pig breed are implicated in shaping gut microbiota. Tibetan pig is a unique native Chinese breed and has evolved to manifest a strong disease resistance. However, the immunity and microbiota of growing Tibetan (TP) pigs were still rarely understood. The jejunal immunity phenotype and microbial composition of TP and Duroc × (Landrace × Yorkshire) (DLY) pigs were explored through immunohistochemistry and 16S rRNA sequencing. Higher scores of clusters of differentiation 4 (CD4+) and Toll-like receptor 9 (TLR9) were observed in TP pigs than those of DLY pigs (p < 0.05), as were Interleukin 10 (IL-10) and zonular occludens 1 (ZO-1) (p < 0.01). Similar levels of bacterial richness and diversity were found in the jejunal microbiota of the TP and DLY pigs. However, the TP pigs showed a significantly different microbiome compared to DLY pigs at the genus level (ANOSIM; p < 0.05). Pseudomonas, Stenotrophomonas, Phenylobacterium and Sandaracinobacter were enriched in DLY pigs (p < 0.05), while the Lactobacillus and Solibacillus had higher abundances in TP pigs than DLY pigs (p < 0.05). Tibetan pigs have “healthier” intestinal microbial communities than DLY pigs. Close relationships were found between jejunal immune performance and the differential bacteria, Lactobacillus can enhance porcine jejunal immunity, while Stenotrophomonas will have a negative impact on porcine gut immunity.